Advanced gravitational wave detectors - Blair, David G. (Cambridge University Press, 2012)
After decades of research, physicists now know how to detect Einstein's gravitational waves. Advanced gravitational wave detectors, the most sensitive instruments ever created, will be almost certain of detecting the births of black holes throughout the Universe. This book describes the physics of gravitational waves and their detectors. The book begins by introducing the physics of gravitational wave detection and the likely sources of detectable waves. Case studies on the first generation of large scale gravitational wave detectors introduce the technology and set the scene for a review of the experimental issues in creating advanced detectors in which the instrument's sensitivity is limited by Heisenberg's uncertainty principle. The book covers lasers, thermal noise, vibration isolation, interferometer control and stabilisation against opto-acoustic instabilities. This is a valuable reference for graduate students and researchers in physics and astrophysics entering this field